Design of piezoelectric self-sensing microinjection device. (April 2019) - Wei, X W; Sun, L P; Su, C; Shi, Y L; Li, J Q
Abstract: With the development of biotechnology and injection technology, cell micro flow syringes have been widely used in many fields. In the meanwhile, the requirements of experimental equipment and experimental method are becoming higher and higher. In this paper, the author study on the theory and experiment of the first direct and secondary converse piezoelectric effects of piezoelectric ceramics by using the piezoelectric characteristics which can realize the integration of sensors and actuators. And the author design a self-sensing micro injection device which has the functions of localization, injection output and self-perception. The control precision and operation have been effectively improved by means of analyzing the relationship between the output and the input.